Effect of surface‐modified montmorillonite incorporated biopolymer membranes for PEM fuel cell applications. (6th December 2017) - Kalaiselvimary, J.; Selvakumar, K.; Rajendran, S.; Sowmya, G.; Ramesh Prabhu, M.
Abstract : Proton Exchange Membranes (PEMs) based on nanocomposite consisting of Chitosan and Poly (ethylene oxide) (PEO)/modified montmorillonite (H + ‐MMT) was prepared by solution casting technique. To appraise PEM performance, the structural properties, hydrolytic stability and transport properties of the prepared membranes were investigated using various characterization methods like FT‐IR, XRD, SEM, AFM, water uptake, swelling ratio, ion exchange capacity (IEC), and proton conductivity measurements. Fabricated blend membranes showed favorable PEM characteristics such as afford comparable proton conductivity, moderate ion exchange capacity and reasonable water uptake. Proton conductivities of the blend membranes are about 2.99 × 10 −2 S/cm at room temperature. All the membranes are homogenous that could be revealed from the XRD studies. All the results obtained from this study can be used to conclude that the Chitosan/PEO membrane with H + ‐MMT filler is a promising high performance PEM candidate for fuel cell applications in future. POLYM. COMPOS., 40:E301–E311, 2019. © 2017 Society of Plastics Engineers